Junctional Zone in Infertile Women: A Three-dimensional Ultrasound Study - Silva, Vanessa; Ramos, Flávia Fundora; Brás, Ana Filipa Matos; Santos, Ricardo Filipe Sousa; Xavier, Maria Sofia Dantas Pinto Lobo; Miguelote, Rui Filipe Oliveira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2020)
Objective To analyze the interobserver and intraobserver reproducibility of the visualization and continuity of the juncional zone (JZ) by three-dimensional (3D) ultrasound in infertile women, and to evaluate the sociodemographic, hormonal, and structural factors that influence these assessments.Methods A prospective study conducted at the Assisted Reproductive Technology Unit of Hospital Senhora da Oliveira, in the city of Guimarães, Portugal. Transvaginal 3D ultrasonography was performed, and 2 volumes were generated per case. Two observers who were blinded to each other's work analyzed these volumes, choosing the best coronal section. Four months later, one of the observers performed the same methodology. The JZ visualization was classified as optimal, satisfactory, and unsatisfactory, and the JZ continuity, as continuous and discontinuous. The interobserver and intraobserver agreements were analyzed. The influence of hormonal, structural, and sociodemographic factors on the JZ was evaluated.Results In total, 65 women were included in the present study. The interobserver reproducibility was substantial for JZ visualization and continuity (k = 0.635 and 0.753 respectively), and the intraobserver reproducibility was very good for JZ visualization and continuity (k = 0.884 and 0.816 respectively). Trilaminar endometrial pattern was associated with optimal JZ visualization (p = 0.012). The increase of 1 unit in the level of serum estradiol represents a 9.9% decrease in the odds of unsatisfactory visualization of the JZ (odds ratio [OR] = 0.9; 95% confidence interval [95%CI] = 0.814–0.996; p = 0.042). Endometriosis increases the odds of unsatisfactory visualization by 24 times (OR = 23.7; 95%CI = 1.262–437.057; p = 0.034). The prevalence of discontinuous JZs was of 60%. Myomas and endometriosis were associated with discontinuous JZs (p = 0.034 and 0.016 respectively).Conclusion The assessment of JZ visualization and continuity by 3D ultrasound is reproducible enough to be used in the clinical practice.
Keywords: 3D ultrasound; junctional zone; reproducibility; infertility; associated factors